Chromosomal microarray analysis in fetuses with aberrant right subclavian artery. (March 2017) - Maya, I.; Kahana, S.; Yeshaya, J.; Tenne, T.; Yacobson, S.; Agmon‐Fishman, I.; Cohen‐Vig, L.; Levi, A.; Reinstein, E.; Basel‐Vanagaite, L.; Sharony, R.
ABSTRACT: Objective: To evaluate the association between aberrant right subclavian artery (ARSA), with or without additional risk factors for aneuploidy or ultrasound abnormality, and results of chromosomal microarray analysis (CMA). Methods: This was a multicenter study of fetuses diagnosed with ARSA that underwent genetic analysis by CMA, all samples being analyzed in the same laboratory. Clinical investigation included nuchal translucency measurement, first‐ and second‐trimester maternal serum screening, early and late second‐trimester fetal anatomy scans and fetal echocardiography. Comparative genomic hybridization microarray analysis or single‐nucleotide polymorphism array technology was used for CMA of DNA samples obtained from amniotic fluid. Results: CMA results were available for 63 fetuses with ARSA. In 36 fetuses, ARSA was an isolated finding, and no pathogenic variant was found. Additional ultrasound findings and/or risk factors for aneuploidy were present in 27 fetuses, five of which had pathogenic CMA results. Of these five, trisomy 21 was detected in a fetus with echogenic intracardiac focus (EIF), 22q11 deletion was detected in a fetus with EIF and an increased risk of trisomy 21 of 1:230 from maternal serum screening, 22q11 duplication was detected in a fetus with hypoplastic right kidney and choroid plexus cyst and 22q11 deletion was detected in a fetus with right aortic arch and clubfoot. The fifth fetus had increased nuchal translucency thickness (4 mm) and a ventricular septal defect, and CMA identified both 22q11 deletion and 1q21 duplication. Conclusions: In fetuses with isolated ARSA, an invasive procedure for CMA is not indicated. However, CMA is recommended when additional ultrasound abnormalities or risk factors for aneuploidy are observed. The chromosomal findings in four of the five cases with an abnormal CMA result in our study would not have been detected by standard fetal chromosomal testing. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.